Stressful life events and occupational accidents - Cordeiro, Ricardo; Dias, Adriano [UNESP] (Scandinavian Journal of Work, Environment and Health, 2005)
Objective: The purpose of this study was to examine the association between stressful life events and occupational accidents. Methods: This was a population-based case-control study, carried out in the city of Botucatu, in southeast Brazil. The cases consisted of 108 workers who had recently experienced occupational accidents. Each case was matched with three controls. The cases and controls answered a questionnaire about recent exposure to stressful life events. Results: Reporting of environmental problems, being a victim of assault, not having enough food at home and nonoccupational fatigue were found to be risk factors for work-related accidents with estimated incidence rate ratios of 1.4 [95% confidence interval (95% CI) 1.1-1.7], 1.3 (95% CI 1.1 1-1.7), 1.3 (95% CI 1.1-1.6), and 1.4 (95% CI 1.2-1.7) respectively. Conclusions: The findings of the study suggested that nonwork variables contribute to occupational accidents, thus broadening the understanding of these phenomena, which can support new approaches to the prevention of occupational accidents.
Keywords: Accident proneness; Distressing event; Risk factor; Wounds and injury epidemiology; accident; health risk; medical geography; occupation; risk factor; working conditions; adolescent; adult; aged; assault; Brazil; case control study; city; confidence interval; controlled study; environmental factor; exposure; fatigue; female; food intake; human; incidence; life event; major clinical study; male; mental stress; occupational accident; phenomenology; population research; priority journal; questionnaire; victim; worker; Accidents, Occupational; Adolescent; Adult; Age Factors; Aged; Case-Control Studies; Female; Humans; Life Change Events; Male; Middle Aged; Occupational Health; Questionnaires; Risk Factors; Sex Factors; Urban Population